Factors determining the optimum moisture content (OMC) of greywacke aggregates from northern New Zealand. (June 2019) - Li, Wentao; Wilson, Douglas J.; Larkin, Tam J.; Black, Philippa M.
Abstract: Using marginal materials with high optimum moisture contents (OMC), is likely to cause significant problems, such as rutting and shoving. To determine the reasons for the high OMC of marginal greywacke aggregates, this study investigated the factors influencing OMCs by determining the particle size distribution, flakiness index, water absorption capacity and clay mineralogical composition of a suite of greywacke aggregates from two greywacke quarries in the North Island of New Zealand (NZ). The results indicated that grading was not a significant factor responsible for the higher OMCs of marginal aggregates in this study. However, the marginal aggregates had higher percentage of flaky particles and higher water absorption capability, which both caused the higher OMCs of the marginal aggregates when compared with the OMCs of premium aggregates. Additionally, swelling clay minerals, e.g. smectite, contained in the marginal aggregates with high water absorption capability also contributed to the higher OMCs of marginal aggregates.